Analisis Kesulitan Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam di SMA N 1 Pantai Cermin Kabupaten Solok - Rezha Hermawati Maber; Rahmi Wiza (AS-SABIQUN, 2022)
This study aims to find out what types of learning difficulties are experienced by students in this material and what factors cause learning difficulties. This research uses qualitative research method with descriptive research type. The research subjects consisted of student representatives, PAI teachers, Bk teachers, students and parents. Data collection instruments used in the form of observation, interviews and documentation. The results show that the types of learning difficulties faced by students are (1) students have difficulty reading the Qur'an, (2) students are slow in understanding learning and (3) students have difficulty controlling their emotions. While the factors that cause learning difficulties in students are two factors, first internal factors, namely low intelligence and interest in learning, second external factors, namely lack of motivation to learn from the family, less varied learning methods, and technology that makes students lazy to learn. As for how the teacher overcomes the learning difficulties of students by the teacher, namely (1) using varied learning methods, (2) remedial lessons, (3) providing motivation to learn and (4) providing additional assignments.